Coping Stress Mechanism: The Relationship Among Role Overload, Role Conflict, and Role Ambiguity Toward Cyberloafing - Rauly Sijabat; Noni Setyorini (Universitas 17 Agustus 1945 Semarang, 2026)
Cyberloafing is viewed as an employee's entertainment when feeling fatigued from various tasks and responsibilities in the workplace. This research aims to examine the influence of Role Overload, Role Conflict, and Role Ambiguity on cyberloafing with job stress. The study utilizes structural equation model (SEM) testing using AMOS software. Data collection is conducted through an online survey with a total of 127 respondents. Based on the test results, it is found that role conflict and role ambiguity do not have an influence on cyberloafing, while job stress and role overload have a positive and significant impact on cyberloafing. Based on the research findings, the practical implications of this study encourage companies to develop and implement more effective stress management and workload policies.